Adição de elementos de liga (boro e nióbio) em ferro fundido branco alto cromo : uma análise comparativa do ganho de resistência ao desgaste abrasivo versus custo - Cláudio Gonçalves de Oliveira (2020)
In the case of mining companies, abrasive wear is the cause of operational problems and generates high costs. High chromium white cast iron alloys have been widely used in mining, as they are a class of materials highly resistant to abrasion with a good cost-benefit ratio. To reduce material wear in mining iron ore transfer chutes, materials of high hardness are sought through changes in the chemical composition and/or heat treatments, and often the increase in cost is not considered. In this study, the abrasive wear resistance of four high chromium white cast iron alloys (25.0% Cr and 3.0% C) with the addition of boron and / or niobium was evaluated through laboratory tests of abrasive wear in rubber wheel, according to Standard ASTM G65 and, through industrial tests with test plates inserted in strategic positions along iron ore transfer chutes. The statistical analysis of the results of the abrasion tests by rubber wheel in the laboratory, using a more advanced linear modeling technique known as multivariate marginal linear model, indicated adequate procedures for testing materials in the field and obtaining more reliable results in the selection of materials for use in iron ore mining. The statistical analysis indicated for high chrome white cast iron alloys, with and without niobium and without the addition of boron, the variation of the abrasive granulometry has the greatest influence on the wear resistance measured of the volumetric losses during the wear. On the other hand, these alloys with the addition of boron, the intensity of the applied force has the greatest influence on the accumulated volumetric losses (in mm³). The abrasive wear resistance of all four alloys was evaluated in field tests through two applications: transfer chute and belt feeder conveyor. These two applications differ essentially in the severity of wear, severe and mild, respectively. The results obtained in the field are in accordance with the conclusions pointed out by the statistical analysis. In high severity, alloys with boron added had the worst performance in terms of wear volumetric loss. In mild severity, these alloys performed better. A new parameter, relative replacement cost (RRC), was developed that considers to evaluate the wear resistance gain related to the increase in alloy cost. It was concluded that the addition of niobium was neither economically justified nor demonstrated a gain on abrasive resistance. The addition of boron was considered beneficial for industrial applications where there is mild severity in the wear process. When the conditions of severity were high, the addition of either niobium or boron to high chromium white cast iron alloys was not economically justified regarding the gain in resistance to abrasive wear, in the case of abrasive iron ore.